مابعد جدید مفکر"ژان فرانکواس لیوتار":" تعارف اورسماجی و علمی شعریات" (Al-Aasar, 2026)
Lyotard shed light on new concepts of knowledge and their practical implications. He examined traditional narrative knowledge in the context of modern societal demands and presented scientific knowledge as a linguistic game. According to him, the task of postmodern science is not to discover certain and eternal truths, but rather to identify and scrutinize instabilities within existing knowledge structures.On the social and political front, Lyotard declared his opposition to all forms of comprehensive systems. He rejected any single, overarching theory, be it Marxism or any other grand narrative. Instead, he emphasized the importance of small, local, and diverse "narratives," which he believed could better express the complexity of human experience .Lyotard highlighted the deep connection between knowledge and power. According to his analysis, in postmodern society, the standard and purpose of knowledge have changed. Knowledge is no longer merely a tool for enlightenment but has become a commodity over which power and control are contested.This article unveils the intellectual context and theories of Lyotard, which will be a contribution to the world of Urdu literature.